Pendekatan Beyond Centers and Circle Time (BBCT) Pada Anak Usia Dini - Soleha, Mela Melati; Anjani, Ratna (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
This article reviews the application of the Beyond Centers and Circle Time (BCCT) approach in Early Childhood Education. BCCT is a child-centered learning method that integrates directed play strategies with center and circle methods. The purpose of this article is to comprehensively explore the concept, implementation, and evaluation of BCCT in the context of Early Childhood Education. The method used is a literature study by reviewing various sources related to BCCT. The main findings reveal that BCCT is effective in optimizing early childhood development holistically through stimulation of multiple intelligences in structured play activities. BCCT implements seven learning centers by utilizing four types of footholds to support children’s growth. In addition, BCCT has a comprehensive evaluation system integrated in the learning process. The contribution of this article in the field of early childhood education is to provide in-depth insight into the application of BCCT as an innovative child-centered approach, so that it can be a reference for educators and stakeholders in optimizing the early childhood learning process.